Minimal Manifestation Status Indicates a Stable State in Myasthenia Gravis: A Quantitative Study - Jiang, Ping; Li, Jie; Li, Hong-Yan; Zhang, Bin; Yue, Yao-Xian; Wang, Su-Yun; Zi, Xi-Cun; Liu, Shuang-Shuang; Li, Yi-Fan; Jiao, Li-Dong; Li, Hai-Feng (Frontiers in Neurology, 2022)
Introduction Minimal manifestation (MM) or better was recommended as the treatment goal for myasthenia gravis (MG). The sustainability of this status has not been described quantitatively in patients who had attained or are close to it. Methods Patients who were with no or slight impact on daily living were recruited and followed at baseline and 3, 6, and 12 months. The included patients were classified into 3 post-intervention status (PIS) categories: remission (R), MM, and slight impact (SI). The proportion of patients belonging to real-time (not considering the intervals between assessments) and sustained (considering the intervals between assessments) PIS categories was compared at each follow-up. A sensitivity analysis (SA) cohort was established by including patients with PIS categories in all four follow-ups. The QMGS, MG-ADL, and MG-QOL15 scores in patients belonging to each PIS category at each follow-up were compared. The sustainability of the R/MM status was examined and correlated with real-time R/MM status at follow-ups. Results At baseline, 376 patients could be classified, including 55 as R (14.2%), 209 as MM (54.0%), and 112 as SI (28.9%). In the whole cohort, 68.8–89.7%, 71–76.7% and 19.8–77.1% of the patients classified into real-time R, MM, and SI categories remained unchanged in each follow-up compared with the previous follow-up. The proportion of patients belonging to each real-time or sustained R/MM status at the three follow-ups was 89.7–92.1 or 60.8–67. In the SA cohort, at least 86.4% of the baseline R/MM patients remained in R/MM status till 12 months. There were no differences in keeping real-time R/MM status at 6 or 12 months between patients with and without sustained R/MM status at 3 and 6 months. There were differences in the QMGS, MG-ADL, and MG-QOL15 scores among patients belonging to each real-time category at baseline and follow-ups, ranking as R < MM < SI. The same trend was observed in patients belonging to each sustained PIS category with smaller scores than the same items of real-time categories. Conclusion The sustainability of the R/MM status was confirmed. The R/MM status indicated a stable state of MG. The QMGS, MG-ADL, and MG-QOL15 scores may provide a quantitative reference for these PIS.